2019
DOI: 10.2147/cia.s224663
|View full text |Cite
|
Sign up to set email alerts
|

<p>12-Month Teriparatide Treatment Reduces New Vertebral Compression Fractures Incidence And Back Pain And Improves Quality Of Life After Percutaneous Kyphoplasty In Osteoporotic Women</p>

Abstract: PurposeDefine the effectiveness of teriparatide (TPTD) treatment on reducing the incidence of new vertebral compression fractures (NVCFs) and back pain and improving quality of life after percutaneous kyphoplasty (PKP).MethodsTwo years of clinical follow-up data from primary osteoporotic women who had experienced initial osteoporotic vertebral compression fractures (OVCFs) and received PKP plus 12-month TPTD (n=113) or basic treatment (BT) of calcium and vitamin D supplements (n=208) were retrospectively colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…In the previous studies, many reports show that the vertebral body height restoration and kyphotic changes are very significant. As a result, PKP could not only stable the fractured vertebra body and reveal the severe pain immediately, but also restore the vertebral body height and correct the local kyphosis by inflating of the balloon (6,9,10). However, there is no study investigate the influence of PKP on the (12)(13)(14).…”
Section: Imaging Results Pre-and Post-operationmentioning
confidence: 99%
“…In the previous studies, many reports show that the vertebral body height restoration and kyphotic changes are very significant. As a result, PKP could not only stable the fractured vertebra body and reveal the severe pain immediately, but also restore the vertebral body height and correct the local kyphosis by inflating of the balloon (6,9,10). However, there is no study investigate the influence of PKP on the (12)(13)(14).…”
Section: Imaging Results Pre-and Post-operationmentioning
confidence: 99%
“…As all we known, zoledronic acid could inhabit osteoclasts differentiate and proliferate, regulate bone metabolism and reduce bone loss. In this article, 6 retrospective studies [32][33][34][35][36][37] and 2 prospective studies [38,39]were searched out. 7 studies [32][33][34][35][37][38][39] reported the effect of ZOL and one study [37] reported the effect of Teriparatide.1416 cases, 574 cases in test group and 842 cases in control group, who had residual pain in back or low back were observed.…”
Section: Improving Osteoporosismentioning
confidence: 99%
“…5,8,[10][11][12][13][14][15][16][17][18][19] Additionally, Kong et al found that patients receiving teriparatide for 12 months after percutaneous kyphoplasty had a lower risk of new vertebral compression fracture and greater improvements in pain and quality of life than placebo at all time points up to 24 months after surgery. 44 While published data has only evaluated teriparatide use in spinal surgery, similar work is ongoing and needed to demonstrate the clinical benefits of abaloparatide.…”
Section: Use In Spine Surgerymentioning
confidence: 99%